Cold-to-electricity conversion using a piston based engine in cold energy storage (CES) system, part one: A theoretical study. Issue 5 (October 2017) - Du, Yanping; Ding, Yulong
Abstract: This study concerns the cold-to-electricity conversion in a piston based engine. A theoretical model was developed to predict the power generation rate in the engine. Parametric study showed the significant effect of p-crank angle, motor speed, gas pressure and temperature and chamber volume on the power generation by the piston based engine. It was found that optimal p-crank angle was normally in the range of 55°∼76°. The minimum inner diameter of the valves connected to the engine was a crucial factor that limited the power capacity of the engine system. Based on the experimental data, the large engine (1900 cm 3 ) and small engine (162 cm 3 ) had an actual efficiency of 24.1% and −23.6%, respectively. This implied that the large engine was feasible to be used in CES system for electricity re-generation during peak hours. However, the induced CES efficiency was 18.9% and 52.1% in two different situations. The results indicate the importance of engine development in promoting the CES technology. Highlights: The optimal p-crank angle which leads to the maximum power generation varies in the range of 55° and 76°. Large engines is feasible to be used in a real CES system due to the positive overall engine efficiency. Due to the low engine efficiency, the energy storage efficiency of the CES system was estimated as 18.9% and 52.1% in two different situations.